KONFLIK BATIN, PSIKOLOGI PENGARANG, DAN HIRAKI KEBUTUHAN DALAM PUISI PROLOGUE KARYA SAPARDI DJOKO DAMONO - Abror, Muchlas; Safitri, isma (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to analyze the inner conflict that exists in Prologue's poems as a reflection of the author's psychology and the needs of Sapardi Sapardi Djoko Damono. The approach used is qualitative. Data collection techniques are carried out through reading, listening, and taking notes. The data was then analyzed through a heterogeneous approach accompanied by a descriptive approach. The author interprets the data as well as describes. The results of the study show that the inner conflict of poetry occurs due to worries about life. Meanwhile, the author's psychological description in the poem is spiritual awareness, contemplation of grief and loyalty, isolation and loneliness, reflective and contemplative ability, sensitivity to space and time, appreciation for words. Meanwhile, related to the hierarchy of needs, the poem describes the need for self-actualization, because Sapardi Djoko Damono is able to live the values of humility, understand limitations, and accept tests with patience and sincerity.